2009
DOI: 10.1038/nature08575
|View full text |Cite
|
Sign up to set email alerts
|

Systems-level dynamic analyses of fate change in murine embryonic stem cells

Abstract: Molecular regulation of embryonic stem cell (ESC) fate involves a coordinated interaction between epigenetic1–4, transcriptional5–10 and translational11,12 mechanisms. It is unclear how these different molecular regulatory mechanisms interact to regulate changes in stem cell fate. Here we present a dynamic systems-level study of cell fate change in murine ESCs following a well-defined perturbation. Global changes in histone acetylation, chromatin-bound RNA polymerase II, messenger RNA (mRNA), and nuclear prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
266
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(284 citation statements)
references
References 37 publications
12
266
2
1
Order By: Relevance
“…Whether this observation is valid in other cell types is not known. A recent study on embryonic stem cells revealed that changes in protein levels are not accompanied by changes in corresponding mRNAs, although this study did not discern translational and post-translational control 38 .…”
Section: Discussioncontrasting
confidence: 79%
“…Whether this observation is valid in other cell types is not known. A recent study on embryonic stem cells revealed that changes in protein levels are not accompanied by changes in corresponding mRNAs, although this study did not discern translational and post-translational control 38 .…”
Section: Discussioncontrasting
confidence: 79%
“…mRNA translation, which is low in undifferentiated embryonic stem cells (ESCs) and multipotent somatic stem cells (e.g., hematopoietic stem cells and skin stem cells), increases significantly during differentiation (3)(4)(5). Importantly, genome-wide analysis of the transcriptome vs. proteome of ESCs during the early stages of differentiation demonstrated that protein levels correlate poorly with mRNA levels (Pearson's R < 0.4), underscoring the importance of posttranscriptional regulation in ESC differentiation (6).…”
mentioning
confidence: 99%
“…Given this switch in expression of the two topo II isozymes when cells transit from actively dividing, pluripotent state to a postmitotic, terminally differentiated state, we were tempted to investigate the stem cell-specific function of TOP2a as well as similarities and differences in targets with TOP2b. Furthermore, given a plethora of factors that are being implicated in the regulation of stem cell pluripotency and differentiation [19][20][21][22][23][24] , we were interested to uncover how these crucial enzymes contribute to this process.…”
mentioning
confidence: 99%